"Aqui a pedra tem vida": um estudo sobre o artesão da Pedra Sabão - Chagas, Tays Torres Ribeiro das (2018)
This work presents a study on craftsmanship with soapstone in Santa Rita, district of Ouro Preto, which cultural heritage includes, among others, handcrafted products. The choice of artisan work with soapstone is due to the fact that the production has a significant social and economic impact, in addition to being a secular cultural manifestation in the region. Soapstone carvings are manufactured through family work carried out in workshops located in backyards. In such spaces, the working conditions are painful, precarious and insalubrity is present, in addition to economic instability related to the high cost of the raw material and the difficulties of selling the artifacts produced. Thus, the purpose of the field trips was to understand, through identification of the hardship experienced by the craftsmen, the dynamics behind their exile and return to the locality and to the work with the stone, which happens periodically among them, and therefore, to understand whether it is a choice, a decision was taken by each one of the individuals, to perpetuate soapstone crafts. From the codes encountered in this study, the relationship between the artisans, the craft and the Stone transcends the difficulties associated with handicraft work. It was possible to notice that the perception of these difficulties is softened by the presence of other factors considered important for them, such as identity, gratitude, and pleasure in the activity. Therefore, the theory elaborated based on the data collected in the field suggests that the learning process of the craft was happened since the childhood of the artisans, as a central factor for consolidating these relationships and, therefore, for the sense of belonging to the locality, to the craft and to the Stone itself. It is in the family nucleus, considered the first community of practice for each one of them, that the knowledge, the skills, the creativity and, therefore, the identity are built and consolidated, transforming the young apprentice into a craftsman and creating a network in which these relationships are fulfilled; work permeated with satisfaction and pride to perpetuate a secular practical knowledge learned from their ancestors. It is in this family nucleus, in this contact, in observing the work of the other, in the stories told and lived and in a permanent generational process of exchange of knowledge that the craftsman is born and the desire to immortalize not only oneself in the work produced, but the whole family generation born and living from the Stone and back the Stone. Consequently, pursuing soapstone craftmanship is a choice made by the craftsmen. They wish to be in the craftwork, in contact with the Stone and with all it provides them with. The research made it possible to report the narrative by the artisans themselves of their work universe, sensitizing both our eyes to the understanding of this craft, as well as each one of them to the importance of what they achieve, besides promoting significant changes in the collective action of the community itself.